Pengembangan Media Pop-Up Book Berbasis Interaktif Pada Materi Rantai Makanan Untuk Meningkatkan Minat Belajar Siswa Di Kelas V Sekolah Dasar - Hikmah, Nur; Nur Latifah (IJPSE Indonesian Journal of Primary Science Education, 2025)
This study aims to develop interactive pop-up book media on food chain material to increase students' interest in learning in elementary schools. The background of the study is the low interest and active participation of students in learning Natural and Social Sciences (IPAS). The research method uses the Research and Development (R&D) approach with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. Pop-up book media is designed to visualize the concept of the food chain interactively and attractively. Validation was carried out by media, material, and language experts with very high results, 82%. The media was implemented through small 92% and large-scale trials 93% on grade V students. The results of the study showed that interactive pop-up book media is effective in increasing students' interest and understanding of food chain material. This study contributes to the development of innovative learning media that can change abstract concepts into concrete, engaging, and easy-to-understand ideas for elementary school students.